2003
DOI: 10.1002/hlca.200390323
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Homochiral Oligopeptides Generated via Phase Separation of Nonracemic α‐Amino Acid Derivatives and Lattice‐Controlled Polycondensation in a Phospholipid Environment

Abstract: Dedicated to Professor Duilio Arigoni on the occasion of his 75th birthday Racemic S-ethyl thioesters of N e -stearoyllysine ( S-ethyl (R,S)-2-amino-6-(stearoylamino)hexanethioate) and S-ethyl thioesters of g-stearyl glutamic acid ( stearyl (R,S)-4-amino-5-(ethylsulfanyl)-5-oxopentanoate) self-assemble as separated two-dimensional crystalline monolayers within an achiral phospholipid environment of racemic 1,2-dipalmitoylglycerol (DPG) and 1,2-dipalmitoylglycero-3-phosphoethanolamine (DPPE), as demonstrated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…Similar results were obtained for the polymerization of nonracemic C18-Lys-TE within a phospholipid environment, where the ethanolamine group of the phospholipid served as the initiator of the reaction [25].…”
Section: Isotactic Oligomers Generated Within Monolayers At the Air-wsupporting
confidence: 77%
See 2 more Smart Citations
“…Similar results were obtained for the polymerization of nonracemic C18-Lys-TE within a phospholipid environment, where the ethanolamine group of the phospholipid served as the initiator of the reaction [25].…”
Section: Isotactic Oligomers Generated Within Monolayers At the Air-wsupporting
confidence: 77%
“…The polymerization of racemic monomers in ideal solutions should result in the formation of atactic polymers where the chains contain monomer residues of both enantiomers [23][24][25]. One way of generating isotactic polymers is to assemble these monomers into crystalline-like aggregates prior to the reaction; the air-water interface provides just such a medium.…”
Section: Isotactic Oligomers Generated Within Monolayers At the Air-wmentioning
confidence: 99%
See 1 more Smart Citation
“…Three structures formed by amphiphiles have been investigated for their potential in promoting peptide formation: bilayers of liposomes [68][69][70][71], micelles [46] and monolayer lattices [72,73]. As for the mineral-supported reactions, substrate monomers can be adsorbed on the amphiphile-structure surface that can easily be functionalized by mixing zwitterionic and charged amphiphiles to yield various surface charge potentials.…”
Section: Amphiphile Structuresmentioning
confidence: 99%
“…± As a part of our studies on the formation of homochiral oligopeptides from nonracemic activated a-amino acid monomers, we have proposed a general mechanism for the amplification of chirality that encompasses a phase separation of the nonracemic monomers into two-dimensional (2D) crystallites, either on H 2 O or within a membrane-like environment of a phospholipid monolayer, followed by a lattice-controlled polymerization. In the preceding article of this journal issue [1], we demonstrated that polycondensation of nonracemic S-ethyl thioesters of both lysine and glutamic acid amphiphiles gives rise to homochiral oligopeptides, when embedded within a phospholipid monolayer, as determined by MALDI-TOF MS of deuteriumenantiolabeled monomers. Grazing-incidence X-ray-diffraction (GIXD) studies of the films composed of an equimolar mixture of racemic phospholipids with racemic thioesters clearly showed a phase separation between 2D crystalline domains of phospholipid and those of the thioesters, very similar to those observed for the pure components.…”
mentioning
confidence: 91%